An atypical sarcoid-like reaction during anti-protein death 1 treatment in a patient with metastatic melanoma. Issue 5 (October 2020) - Keukeleire, Stijn De; Schwarze, Julia; Awada, Gil; Everaert, Hendrik; Van Binst, Anne Marie; Cras, Louise; Neyns, Bart; Aspeslagh, Sandrine
Abstract : We report a case of anti-protein death 1-induced sarcoid-like reaction in a 63-year-old Caucasian male who was diagnosed with stage IV-M1a melanoma. He was initially treated with pembrolizumab monotherapy (Q3W) and had a complete response after 14 cycles. However, relapse was suspected 3 months later with appearance of hilar, mediastinal and hepatic hilar lymph nodes as well as a skin lesion. Biopsy of both the hilar lymph nodes and the skin lesion demonstrated sarcomatoid granulomatosis. Pembrolizumab was discontinued temporarily. While on 18 F-FDG-PET/CT, all sarcoid-like lesions regressed in size and activity, a new hypermetabolic solitary skeletal lesion was detected in a lumbar vertebra, suspicious for metastasis. However, since the patient was asymptomatic, a watchful-waiting attitude was taken. During this period, a spontaneous and complete resolution of the metabolic activity was observed of the skeletal lesion. Until today, the patient remains in complete remission. Current case presents an atypical presentation and evolution of anti-PD-1-induced sarcoid-like reaction, illustrating the difficulty of differentiating it from disease progression. Before considering (re-)initiation of anti-melanoma therapy, a tissue biopsy of one of the suspected lesions may be performed to confirm diagnosis. Physicians treating patients with ICI should be aware of this difficulty and critically assess the nature of lesions suspect of progression in patients responding to ICI and presenting with a sarcoid-like reaction.